2020
DOI: 10.1186/s12889-020-8263-2
|View full text |Cite
|
Sign up to set email alerts
|

A community-wide acute diarrheal disease outbreak associated with drinking contaminated water from shallow bore-wells in a tribal village, India, 2017

Abstract: Background: In 2016, India reported 709 acute diarrheal disease (ADD) outbreaks (> 25% of all outbreaks). Tribal populations are at higher risk with 27% not having accessibility to safe drinking water and 75% households not having toilets. On June 26, 2017 Pedda-Gujjul-Thanda, a tribal village reported an acute diarrheal disease (ADD) outbreak. We investigated to describe the epidemiology, identify risk factors, and provide evidence-based recommendations. Methods: We defined a case as ≥3 loose stools within 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…The presence of these organisms in the wells has the potential to subject the people living in this vicinity to a lot of gastroenteritis. This is supported by (Loyola et al, 2020;Maramraj et al, 2020;Fakhr et al, 2016) that faecal contamination of drinking water is a frequent problem which accounts for many cases of diarrhoea. This may explain the reports gathered from the Tano North District Health Directorate (2011) in Awuah (2012) indicating that many people in the Districts complain of typhoid and other diarrhoea related diseases.…”
Section: Results and Discussion Lateral Separation And Microbial Countsmentioning
confidence: 90%
“…The presence of these organisms in the wells has the potential to subject the people living in this vicinity to a lot of gastroenteritis. This is supported by (Loyola et al, 2020;Maramraj et al, 2020;Fakhr et al, 2016) that faecal contamination of drinking water is a frequent problem which accounts for many cases of diarrhoea. This may explain the reports gathered from the Tano North District Health Directorate (2011) in Awuah (2012) indicating that many people in the Districts complain of typhoid and other diarrhoea related diseases.…”
Section: Results and Discussion Lateral Separation And Microbial Countsmentioning
confidence: 90%
“…Cholera is mostly an easily transmittable disease from person to person contact with the infected case or by contaminated materials (10). Several existing studies have found that a history of contact with infected patients increases the risk of cholera disease transmission from an infected person to another through contact by 4 to 5 times, and the risk is even higher among household contacts (30,32). Our ndings also revealed that exposure to cholera cases in the sub-city was statistically signi cant to the disease and was a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Poor coverage of sewerage system, especially in rural areas, calls for on-site and safe containment and management of faecal waste. Faecal matter, when dumped in the open-land environment (near households), affects public health and results in contamination of soil and water resources (Sarkar et al 2016;Nath & Sharma 2017;Reese et al 2019;Roy & Pramanick 2019;Subbalakshmi et al 2020;Bindra et al 2021). This also leads to bacterial contamination impacting water quality, especially in shallow aquifers.…”
Section: Sanitation Sectormentioning
confidence: 99%